2014
DOI: 10.1111/cea.12394
|View full text |Cite
|
Sign up to set email alerts
|

Differential modification of genetic susceptibility to childhood eczema by two probiotics

Abstract: This is the first study to show an effect of a probiotic on reducing eczema risk amongst those with particular eczema-associated genotypes. Our findings suggest that Lactobacillus rhamnosus HN001 may be particularly effective in preventing eczema in children with specific high-risk genotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 53 publications
(80 reference statements)
1
20
0
Order By: Relevance
“…in the HN019 group had significantly reduced risks of eczema compared with infants who received placebo. 18 Several of these eczema gene variants occur in genes encoding proteins involved in the immune system, suggesting that HN001 supplementation particularly benefits those with a genetic predisposition towards a less balanced Th1/Th2 response. Other eczema gene variants which interacted with probiotic supplementation occurred in genes encoding proteins involved in skin barrier function such as DEFB1 and SPINK5, indicating a particular benefit of HN001 for those with a genetic predisposition towards poorer skin (and intestinal epithelial) barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…in the HN019 group had significantly reduced risks of eczema compared with infants who received placebo. 18 Several of these eczema gene variants occur in genes encoding proteins involved in the immune system, suggesting that HN001 supplementation particularly benefits those with a genetic predisposition towards a less balanced Th1/Th2 response. Other eczema gene variants which interacted with probiotic supplementation occurred in genes encoding proteins involved in skin barrier function such as DEFB1 and SPINK5, indicating a particular benefit of HN001 for those with a genetic predisposition towards poorer skin (and intestinal epithelial) barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…Because they are more resistant to harsh environmental conditions, strains of B. animalis subsp. lactis have been studied more than those of other members of the genus Bifidobacterium, and clinical studies demonstrated their healthpromoting attributes in some gastrointestinal disorders and allergic processes (4)(5)(6).…”
mentioning
confidence: 99%
“…The hypothesis that probiotics may be used in the management of allergic disease and eczema was supported by evidence that the composition of intestinal microbiota in children affected by allergic disease and/or eczema was different than the gut microbiota of healthy subjects, and often these differences have been observed to precede the development of the aforementioned diseases (Watanabe et al, 2003). Morgan et al (2014) investigated whether the probiotic microorganisms Lactobacillus rhamnosus and Bifidobacterium animalis subsp, lactis were able to modify the genetic predisposition to eczema conferred by genetic variation in susceptibility genes in children. Morgan et al (2014) investigated whether the probiotic microorganisms Lactobacillus rhamnosus and Bifidobacterium animalis subsp, lactis were able to modify the genetic predisposition to eczema conferred by genetic variation in susceptibility genes in children.…”
Section: Probiotics: An Innovative Therapeutic Strategymentioning
confidence: 99%
“…As a consequence, the intestinal dysbiosis may cause or worsen allergic diseases, reinforcing the hypothesis that probiotic bacteria may be used for the prevention and treatment of allergies and eczema. It is possible that some probiotics microorganisms are able to readjust the immune system away from a proallergic response, while others may exert their action in overcoming the defects in skin barrier as a result of genetic variation in genes, such as DEFB1 and SPINK5, which encode epidermal and epithelial structural proteins, respectively (Morgan et al, 2014). The authors observed that children who carried a genetic variant that put them at a higher risk of developing eczema were significantly less susceptible to develop eczema if they took the L. rhamnosus strain, compared to those who took the B. lactis strain or children in the placebo group.…”
Section: Probiotics: An Innovative Therapeutic Strategymentioning
confidence: 99%
See 1 more Smart Citation